The Role of Social Media in Marketing Tourism Halal to the International Market Challenges and Opportunities - Nurmaizar, Siti; Widodo, Slamet (Yayasan Sinergi Kawula Muda, 2024)
This research aims to determine people's behavior regarding the use of social media as a source of information and knowledge about halal as well as the role of social media and its function as a means of marketing halal tourism to the international market. This research was conducted using quantitative methods with an associative approach. Data collection techniques using questionnaires, interviews and observation. The population used in this research was 560 respondents. And the samples used were 132 samples. The results of this research found that social media plays a positive and significant role in marketing halal tourism to the international market. The conclusion of this research is that social media has a positive and significant effect on marketing halal tourism to international markets. The suggestion in this research is to increase the marketing of halal tourism to the international market, so that social media promotion via TikTok and Histagram media is very effective and efficient, so it needs to be developed optimally.